Transitions in the energy system: The strategies of new firms commercializing advanced renewable energy technologies - Fontes, M. (2013)
The paper discusses the entry strategies adopted by research-based firms introducing advanced renewable energy technologies in the electricity production sector. Because these firms operate in an environment that combines fast technological change and strong incumbent power, this provides a good setting to address the interactions between niche innovators and regime incumbents. Drawing on contributions from the literatures on sustainability transitions and on strategic management of technology we build an analytical framework to address the conditions faced by the new entrants, the strategies they adopt, the nature the relationships they establish with incumbents and the attitudes of the latter towards their technologies. This framework is applied through in-depth case studies of new firms in two energy niches that display different levels of technological maturity: wind and wave energy. The paper presents preliminary results from a first set of case studies, which provide some insights into the “commercialisation environment” prevailing in those fields. They suggest that research-based firms tend to depend on the complementary assets possessed by incumbents, but have conditions to protect their technologies; and that the technology is relevant for (at least some) incumbents, which show interest on them, or are directly involved in their development/use. This is, in most cases, conducive to “cooperation” strategies, which assume different forms, according to the stage of development of the technology and its proximity to incumbent competences and business models. The results, although still preliminary, contribute to a better understanding of how these firms act to introduce their technologies, how they relate with regime actors and how the conditions found in the particular environment where they operate influence their potentially disruptive behaviour. Thus, they adds to our knowledge about the role of entrepreneurial firms in energy transitions and provide some insights into nature of the (business-level) niche-regime interactions that take place along these processes.